PEMBELAJARAN MELALUI MODUL BERBASIS KONSTRUKTIVISME DALAM UPAYA MENGATASI MISKONSEPSI PESERTA DIDIK PADA KONSEP SEL DI SMA NEGERI 2 SABANG - Dini Fitria; Muhibbuddin Muhibbuddin; Safrida Safrida (Biotik, 2017)
This study was designed to determine the effort of learning through constructivism-based module to overcome student’s misconceptions of Cell concept in SMAN 2 Sabang. The data collection was conducted in 2016, July to August. The method used in this research was quasi-experimental with one group pretest posttest design. The research was conducted in three classes, i.e. XI IA 1, 2 and 3 with 80 students in total. The instrument used was constructivism-based module and pretest-posttest diagnostic tests with CRI answer sheet to assess the comprehension levels of students. Data was analyzed using the percentage formula. Analysis for student’s comprehension showed 69.20% students understand the concept, 25.65% didn’t understand the concept and 5.15% of students experiencing misconceptions. It was concluded that learning through constructivism-based module was effective in order to overcome student’s misconceptions of cell concepts in SMAN 2 Sabang.